Enhancing Religiosity and Building a Religious Culture: The Role of Ma'had al-Jāmi'ah at the Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung - Nasichin Al Muiz, Mochamad; Machali, Imam (Jurnal Pendidikan Islam, 2023)
Purpose – This study examines the impact of Ma'had al-Jāmi'ah in enhancing religiosity and building a religious culture at the Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung. It highlights the necessity for Islamic higher education institutions to balance academic excellence with the development of religious and moral values amidst the challenges of globalization, westernization, and radicalization. Design/methods/approach – This research employs an exploratory descriptive-qualitative design, focusing on Ma'had al-Jāmi'ah at UIN Sayyid Ali Rahmatullah Tulungagung. Data were collected through field research, including observations, in-depth interviews with students, lecturers, and administrative staff, as well as document analysis. Stark and Glock’s five dimensions of religiosity—belief, practice, knowledge, experience, and consequences—served as the analytical framework. Findings – The study found that Ma'had al-Jāmi'ah significantly enhances students' religious knowledge and practices, promoting a balanced integration of Islamic values and academic skills. This institution successfully fosters a religious culture through prescriptive measures and structured learning processes. However, challenges remain due to the diverse backgrounds and varying levels of religious understanding among students. Research implications – The findings suggest that Islamic higher education institutions must integrate religious education with the academic curriculum to foster holistic student development. Regular assessment and adaptation of religious education programs are necessary to maintain their relevance and effectiveness. These findings can guide policymakers and educators in developing comprehensive educational strategies that address contemporary challenges while upholding Islamic values.